The Applicaton of Flipped Classroom Learning Model of High School Students on Electrolyte and Non-Electrolyte Solutions - Yeyet Sri Rahmi; Daud Karel Walanda (Universitas Pakuan, 2022)
The purpose of this study was to determine the differences in the application of the Flipped Classroom learning model and the conventional learning model to student learning outcomes to class X SMA Negeri 1 Paleleh on electrolyte and non-electrolyte solutions. This research was a quasi-experimental research design whiten non-randomized pretest posttest control group design. The population of this study were all students of class X SMA Negeri 1 Paleleh. The sampling technique is random sampling. The sample of this research is class X IPS 3 as the experimental class as many as 27 students and class X MIPA 1 as the control class as many as 26 students. The learning outcomes obtained by the average value of the experimental class are 70.19 and the control class is 64.81. Testing the data from the first research, namely the test using the effect size by Cohen's d, it was found that in the experimental class the Flipped Classroom learning model applied to affect student learning outcomes greater than 97.7% or the effect was very large, while in the control class the conventional learning model applied to affect the results. Student learning as much as 94.5% or a big effect. The second uses a two-party t-test statistical analysis with prerequisite tests, normality tests, and homogeneity. The results of hypothesis testing are obtained – ttable tcalculation + ttable, was -2007 2.9069 +2.007 with a significant level (α = 0.05) and degrees of freedom = 51.